Validity and reliability of the G-Cog BMX Powermeter - Bertucci, W.; Crequy, S.; Chiementin, X. (International Journal of Sports Medicine, 2013)
The aim of this study was to test the validity and reliability of the G-Cog which is a new BMX power meter allowing for the measurements of the power output (250 Hz) at the BMX rear wheel during actual cycling and laboratory conditions. Sprints in road cycling (6-8 s) from static start and incremental tests in the laboratory (100-400 W) have been performed to analyse the validity and reliability of the power output values by comparison with 2 devices: The PowerTap and the SRM which are considered as the gold standard. The most important finding of this study is that the G-Cog power output data were not valid and reliable during sprint and standardised laboratory tests compared with the SRM and the PowerTap devices. During the sprint and the laboratory tests the ratio limits of agreement of the power output differences between the SRM and G-Cog were 1.884×÷1.970 (95%CI=0.956-3.711) and 12.126×÷16.281 (95%CI=0.745-197.430), respectively. In conclusion, the G-Cog must be used with caution regarding the power output measurements. Nevertheless, the G-Cog could be used for the first time to analyse the determinants of the BMX performance from the pedalling profile.